2013
DOI: 10.1016/j.vaccine.2012.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B specific T cell immunity induced by primary vaccination persists independently of the protective serum antibody level

Abstract: In 2005, in accordance with recommendations made by the European Medicines Agency, the Italian Drug Agency ordered withdrawal of the hexavalent Hexavac(®) vaccine (Sanofi Pasteur MSD) from the market. Concerns had been raised about the low immunogenicity of the hepatitis B virus component of the vaccine, assessed by measurement of serum antibody levels, and its potential consequences on long-term protection against hepatitis B infection. We evaluated memory T cell response to establish whether there are differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 36 publications
5
33
0
2
Order By: Relevance
“…5 Recent data suggest the presence of cellular immunity in vaccinated individuals without residual antiHBs. 6,7 Although the role of cellular immunity is not well understood, epidemiological data show that individuals not infected at the time of vaccination almost never develop acute clinical or chronic hepatitis B. 5,8 In conclusion, our results and those from Spradling et al suggest that there is no need for boosters in vaccinated individuals with residual anti-HB antibodies.…”
Section: Short-and Long-term Effects Of a Challenge Dose Of Hepatitissupporting
confidence: 57%
“…5 Recent data suggest the presence of cellular immunity in vaccinated individuals without residual antiHBs. 6,7 Although the role of cellular immunity is not well understood, epidemiological data show that individuals not infected at the time of vaccination almost never develop acute clinical or chronic hepatitis B. 5,8 In conclusion, our results and those from Spradling et al suggest that there is no need for boosters in vaccinated individuals with residual anti-HB antibodies.…”
Section: Short-and Long-term Effects Of a Challenge Dose Of Hepatitissupporting
confidence: 57%
“…Further epidemiological data support the notion that HBV-specific memory T cells might compensate for a lack of humoral protection (15).…”
Section: Introductionmentioning
confidence: 62%
“…Other studies reported a lack of T cell proliferative responses to HBsAg among nonresponders to HBV vaccine booster dose (19)(20)(21). Although one study reported that infant nonresponders to primary vaccination secreted less IFN-g than responders (22), the correlation between anti-HBs levels and IFN-g production remained inconclusive, as this finding was confirmed in some (23) but refuted in other studies (14,24,25). In one study in infants, nonresponders to primary vaccination against HBV secreted less IL-10 than responders (22).Similar results have been observed in adult populations (23,26,27).…”
Section: Introductionmentioning
confidence: 99%